Diagnostic reference level of radiation dose and image quality among paediatric CT examinations in a tertiary hospital in Malaysia - Muhammad, Nor Azura; Abdul Karim, Muhammad Khalis; Abu Hassan, Hasyma; Ahmad Kamarudin, Mazliana; Hsiu, Jeannie Ding Wong; Ng, Kwan Hoong (Multidisciplinary Digital Publishing Institute, 2020)
Pediatrics are more vulnerable to radiation and are prone to dose compared to adults, requiring more attention to computed tomography (CT) optimization. Hence, diagnostic reference levels (DRLs) have been implemented as part of optimization process in order to monitor CT dose and diagnostic quality. The noise index has recently been endorsed to be included as a part of CT optimization in the DRLs report. In this study, we have therefore set local DRLs for pediatric CT examination with a noise index as an indicator of image quality. One thousand one hundred and ninety-two (1192) paediatric patients undergoing CT brain, CT thorax and CT chest-abdomen-pelvis (CAP) examinations were analyzed retrospectively and categorized into four age groups; group 1 (0-1 year), group 2 (1-5 years), group 3 (5-10 years) and group 4 (10-15 years). For each group, data such as the volume-weighted CT dose index (CTDIvol), dose-length product (DLP) and the effective dose (E) were calculated and DRLs for each age group set at 50th percentile were determined. Both CT dose and image noise values between age groups have differed significantly with p-value < 0.05. The highest CTDIvol and DLP values in all age groups with the lowest noise index value reported in the 10-15 age group were found in CT brain examination. In conclusion, there was a significant variation in doses and noise intensity among children of different ages, and the need to change specific parameters to fit the clinical requirement.